EFFECT OF AZADIRACHTICA INDICA LEAVES AQUEOUS EXTRACT ON ERYTHROMYCIN INDUCED HEPATIC DAMAGE - Nausheen Adnan; Iffat Raza; Tahira Assad; Mahrukh Kamran; Sahar Mubeen; Fauzia Perveen (ziauddin University, 2024)
Background: Erythromycin, a commonly used antibiotic for various respiratory tract infections, is well documented for its hepatotoxic effect, which is probably due to the oxidative stress produced by this drug. Azadirachtica Indica, commonly known as Neem is a rich source of various bioactive compounds and has shown strong antioxidant effect in various researches. This study was designed to find out the effect of aqueous extract of Neem leaves on liver enzymes; Alanine transaminase (ALT) and Aspartate transaminase (AST) against liver damage caused by erythromycin. Methods: This study was conducted in Baqai Medical University, Karachi in 2017 spanning a period of 6 months. Eighty male albino wistar rats were taken randomly and were divided into 4 groups of 20 animals each; A(control), B (received erythromycin 100mg/kg body weight), C (received erythromycin 100mg/kg body weight plus aqueous Neem Extract at the dose of 500mg/kg body weight) and "D" (received only aqueous Neem Extract at 500mg/kg body weight). After 14 days of continuous treatment, rats were sacrificed and the blood samples were collected via cardiac puncture and then sent to the laboratory for the investigation of liver enzymes ALT and AST using standard reagent kits. Results: Serum ALT and AST enzymes were found to be decreased in group B and C. The results were Statistically significant. Conclusion: Azadirachtica Indica aqueous extract showed protective effect on erythromycin induced hepatic damage.